2020
DOI: 10.1111/acer.14283
|View full text |Cite
|
Sign up to set email alerts
|

The Addictions Neuroclinical Assessment Negative Emotionality Domain Among Treatment‐Seekers with Alcohol Use Disorder: Construct Validity and Measurement Invariance

Abstract: Background The Addictions Neuroclinical Assessment (ANA), a framework for measuring heterogeneity in alcohol use disorder (AUD), focuses on 3 domains that reflect neurobiological dysfunction in addiction and correspond to the cycles of addiction: executive function, incentive salience, and negative emotionality. Kwako and colleagues (Am J Psychiatry 176:744, 2019) validated a 3‐factor model of the ANA with neuropsychological and self‐report indicators among treatment‐seekers and non–treatment‐seekers with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 43 publications
(66 reference statements)
2
36
0
Order By: Relevance
“…It is likely that differences in specific assessments contributed to the differences in the measurement structure of the model. Notably, our model of the emotionality factor is consistent with recent work that also found that depression and anxiety loaded together onto a negative emotionality factor (Votaw et al, 2020) providing further evidence for this factor structure. Importantly, our study utilized the DASS to assess depression, which is a self‐report assessment of depressive symptomology over the previous week.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is likely that differences in specific assessments contributed to the differences in the measurement structure of the model. Notably, our model of the emotionality factor is consistent with recent work that also found that depression and anxiety loaded together onto a negative emotionality factor (Votaw et al, 2020) providing further evidence for this factor structure. Importantly, our study utilized the DASS to assess depression, which is a self‐report assessment of depressive symptomology over the previous week.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it is unclear how this framework functions to predict current levels of alcohol consumption. While a detailed study of the negative emotionality domain has shown that this factor is related to reasons for drinking and to drinking patterns, this was not compared across factors (Votaw et al, 2020). Given this, the purpose of the current study was 2-fold.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies based on knowledge of substance-related addictions ( Addicott, 2020 ; Votaw et al, 2020 ), however, research related to behavioral addiction is much more scarce, highlighting those focused on understanding the relationship between addictive behavior and activation of the Dorsolateral Prefrontal Cortex and its effects on working memory and inhibition of the control of impulsive responses ( Alizadehgoradel et al, 2020 ; Maheux-Caron et al, 2020 ). One of the behavioral addictions that has attracted the most attention in recent years is pornography addiction.…”
Section: Introductionmentioning
confidence: 99%
“…65 Still considering the changes in the brain induced by PSU, dopaminergic dysfunction in reward circuits seems to lead to dysfunctions in the orbitofrontal cortex. 35 This region has been implicated in the impulsivity observed in psychoactive substance users, 66 as ascertained in many studies in subjects with high anger scores. This is particularly interesting in understanding these results, as the orbitofrontal cortex is anatomically connected to sensory, limbic, and prefrontal cortical regions 67 -areas affected by drug use and which mediate executive function.…”
Section: Discussionmentioning
confidence: 97%